2014
DOI: 10.1021/ja502425t
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Water Oxidation and Origin of Nonaqueous Uranyl Peroxide Complexes

Abstract: Sunlight photolysis of uranyl nitrate and uranyl acetate solutions in pyridine produces uranyl peroxide complexes. To answer longstanding questions about the origin of these complexes, we conducted a series of mechanistic studies and demonstrate that these complexes arise from photochemical oxidation of water. The peroxo ligands are easily removed by protonolysis, allowing regeneration of the initial uranyl complexes for potential use in catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 42 publications
(28 reference statements)
10
57
0
Order By: Relevance
“…This yellow precipitate is characterised as a uranyl-and peroxo-containing oligomer, as ions in the mass spectrum that correspond to [(U VI O 2 ) 2 (μ-O 2 )(NO 3 ) 3 ] À (758.0274 Da) and [(U VI O 2 ) 2 (μ-O 2 )(NO 3 ) 3 (Ph 2 phen)] À (1090.1711 Da) are found. Bands in the Raman spectrum at 838 and 849 cm À 1 ( Figure S7) also compare well with the peroxobridged complex, [{U VI O 2 (NO 3 )(py) 2 } 2 (μ-O 2 )]·py [24] , which has a symmetric μ-O 2 stretch at 860 cm À 1 . Other reported uranylperoxo oligomers have Raman bands between 820 and 870 cm À 1 .…”
supporting
confidence: 53%
“…This yellow precipitate is characterised as a uranyl-and peroxo-containing oligomer, as ions in the mass spectrum that correspond to [(U VI O 2 ) 2 (μ-O 2 )(NO 3 ) 3 ] À (758.0274 Da) and [(U VI O 2 ) 2 (μ-O 2 )(NO 3 ) 3 (Ph 2 phen)] À (1090.1711 Da) are found. Bands in the Raman spectrum at 838 and 849 cm À 1 ( Figure S7) also compare well with the peroxobridged complex, [{U VI O 2 (NO 3 )(py) 2 } 2 (μ-O 2 )]·py [24] , which has a symmetric μ-O 2 stretch at 860 cm À 1 . Other reported uranylperoxo oligomers have Raman bands between 820 and 870 cm À 1 .…”
supporting
confidence: 53%
“…In order to identify the origin of the oxo groups present in complex 1,the anhydrous precursor [UO 2 I 2 (Py) 3 ]was reacted with one equivalent of potassium benzoate in pyridine under fluorescent light. Proton NMR spectroscopy indicated that this reaction does not lead to the formation of 1.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…This cluster is only the second example of aU VI /U V cluster and the first one associating uranyl groups to anon-uranyl(V) center.The U V center in 1 is stable,while the reaction of uranyl(V) iodide with potassium benzoate leads to immediate disproportionation and formation of the U 12 IV U 4 V O 24 cluster {[K(Py) 2 ] 2 [K(Py)] 2 [U 16 O 24 (PhCOO) 24 -(Py) 2 ]} (5).Actinide oxo clusters are important because of their impact on actinide migration in the environment. [1] Thep hotolytic reduction of uranyl(VI) has attracted large interest due to its relevance in spent nuclear fuel reprocessing [2] and storage [3] and to its potential application in catalysis. [4] Early studies reported spectroscopic evidence showing that metastable U V species are produced by photolysis of alcoholic solutions of uranyl(VI) and can be stabilized with respect to disproportionation at high uranyl(VI) concentration by U V /U VI cluster formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of peroxide compounds from the photolysis of uranyl(VI) in the presence of water has also been reported . Most reports suggest that peroxide formation involves water oxidation by a light‐generated excited *UO 2 2+ to yield H 2 O 2 and the reduced pentavalent uranyl species UO 2 + that is subsequently reoxidized by O 2 or may disproportionate to yield UO 2 2+ and U IV species.…”
Section: Figurementioning
confidence: 99%